Tinjauan Yuridis Pengaturan Rapid Test Antigen dan Polymerase Chain Reaction (PCR) Corona Virus Disease-19 dalam Hukum Positif di Indonesia - Putri, Fajria Indah; Firdaus, Emilda; Diana, Ledy (Peneliti.net, 2024)
The entry of Covid-19 requires the government to make policies and regulations. A number of existing rules cannot in fact be in accordance with what is mandated in the Article. The goal of this study are to knowing the regulation of Rapid Test and Polymerase Chain Reaction (PCR) Corona Virus Disease-19 in positive law in Indonesia and the rules of Rapid Test and Polymerase Chain Reaction (PCR) in Positive Law are in accordance with the theory of Legislation Formation. This research was prepared using a normative legal method that focuses on vertical legal synchronization. As a result, the creation of rules regarding the use of rapid antigen and PCR tests through the Decree of the Minister of Health needs to be strengthened and expanded again considering that this Ministerial Decree is limited to recognition and has not touched a more substantive dimension of protection and the regulations and policies issued regarding rapid antigen and PCR tests do not have permanent legal force and are weak and also not in accordance with existing positive law. The Government should pour regulations in one format of laws and regulations that are included in the hierarchy of laws and regulations